(untitled) (Conferencea, 2024)
In the given article the author considers function and levels of modern pedagogues while teaching military vocabulary, also regards training functions of ideal pedagogies in military service, knowing of pedagogical theory, possession of pedagogic mastery, knowing of psychology, possession of teaching techniques and upbringing training stimulate militaries intellectual and cultural developing. Specialists who know their affair are support and future of our Armed forces.